Marketing Automation in Academic Literature: A Systematic Analysis of its Definitions and Categories - Pamungkas, Benni Ahdiyana; Mahardhika, Dhimas; Marniwati, Marniwati (Journal of Economics and Business UBS, 2025)
Marketing automation has become increasingly critical in contemporary business practices, with the global market reaching $6.5 billion in 2023 and projected to grow to $9.5 billion by 2027. However, academic literature currently presents fragmented and diverse definitions of marketing automation, creating both theoretical ambiguity and practical confusion in understanding this construct. This conceptual inconsistency hinders scholarly discourse and impedes practitioners’ ability to make informed decisions regarding technology adoption and implementation. The purpose of this study is to determine the definition of marketing automation based on existing literature. A systematic literature review (SLR) was conducted, and 12 articles on marketing automation were obtained. The results indicate four categories of marketing automation discussions based on definitions. From a theoretical perspective, this study contributes to conceptual clarity by synthesizing fragmented definitions into a coherent framework, while from a practical standpoint, it provides business practitioners with a structured understanding to guide investment decisions and implementation strategies in marketing automation technology. This study clarifies the diversity of marketing automation definitions based on academic literature, which can serve as a theoretical basis for further research and as a foundation for practical digital-based decision-making.